Composition and Seasonality of Membrane Transporters in Marine Picoplankton - Hagström, Åke; Zweifel, Ulla Li; Sundh, John; Osbeck, Christofer M. G.; Bunse, Carina; Sjöstedt, Johanna; Müller-Karulis, Bärbel; Pinhassi, Jarone (Frontiers in Microbiology, 2021)
In this study, we examined transporter genes in metagenomic and metatranscriptomic data from a time-series survey in the temperate marine environment of the Baltic Sea. We analyzed the relative abundance, taxonomic distribution and diversity of transporters in the 3µm - 0.2µm fraction that included prokaryotes and picoeukaryotes. The presence of specific transporter traits was shown to be guiding the seasonal succession of these microorganisms. A limited number of taxa were associated with the dominant transporter proteins that were identified for the nine most important substrate groups. Throughout the year the microbial taxa at the level of order showed highly similar “fingerprint” patterns in terms of transporter functionalities. The relative distribution of transporters stayed the same, irrespective of the abundance of each taxon. This would suggest that the distribution pattern of transporters depend on the bacterial groups being dominant at a given time of the year. Also, we find notable numbers of secretion proteins, that may allow marine bacteria to infect and kill prey organisms thus releasing nutrients. Finally, we demonstrate that transporter proteins may provide clues to the relative importance of biogeochemical processes and we suggest that virtual transporter functionalities may become important components in future population dynamics models.